Mega bentos Studi Jenis-Jenis Fauna Mega Bentos Yang Mendiami Daerah Terumbu Karang Alung Banua Pulau Bunaken Sulawesi Utara - Gumolili, Youdy Joseph Hendrik; Karauwan, Maykel A.J; Rompas, Margresye; Solang, Jeanlly A (PolimdoSains, 2024)
Alung Banua is a coral reef area in the Bunaken National Park area which has coral reef formations and very interesting types of biota. With steep, wall-type reef topography, this area is named after the village of Alungbanua. This research aims to 1) determine the types of mega benthic fauna that inhabit the Alungbanua coral reef area, 2) to determine the diversity and dominance of the mega bentic fauna that inhabits the Alung banua coral reef area. The belt transect method was used to obtain data regarding the mega benthic fauna. Keywords: Alungbanua, Mega benthic.